Nitrogen doped carbon spheres from Tamarindus indica shell decorated with vanadium pentoxide; photoelectrochemical water splitting, photochemical hydrogen evolution & degradation of Bisphenol A. (January 2022) - Parashuram, L.; Prashanth, M.K.; Krishnaiah, Prakash; Kumar, C.B. Pradeep; Alharti, Fahad A.; Kumar, K. Yogesh; Jeon, Byong-Hun; Raghu, M.S.
Abstract: At present energy and environmental remediation are of highest priority for the well defined sustainability. Multifunctional materials that solve both the issues are on high demand. In the present work, a simple method has been followed to extract carbon spheres from Tamarindus indica (commonly known astamarind fruit) shelland doped with nitrogen (N-CS). Vanadium pentoxide nanoflakes were decorated aroundN-CS and the resultant is labeled as V2 O5 /N-CS nanocomposite. The spectroscopic, microscopic, elemental mapping and x-ray photoelectron spectroscopic characterization confirm the nitrogen doping and formation of hybrid material. N-CS, V2 O5, and V2 O5 /N-CS nanocompositehave been evaluated for their efficiency to evolve hydrogen and for degradation of Bisphenol A (BPA) under visible light. In addition, electrocatalytic hydrogen evolution in presence of light has also been evaluated. The DRS spectrum proves the decrease in the bandgap of V2 O5 upon its decoration around N-CS material. In a photochemical experiment, the V2 O5 /N-CS nanocomposite evolved 18, 600 μmolg −1 of H2. Electrochemical hydrogen evolution has also been evaluated in presence of light and obtained the onset potential of −60mV with 52 mV dec −1 Tafel slope value. Scavenger studies indicate superoxide radicals and hydroxyl radicals are the active species responsible for the degradation of BPA. BPA degradation pathway has been predicted with the support of LC-MS results of the intermediates. All these results indicate the synthesized nanocomposite could be an efficient, stable multifunctional material for photocatalytic applications. Graphical abstract: Image 1 Highlights: Carbon spheres synthesis from Tamarindus indica waste shell doped with N. Decoration of V2 O5 nanoflakes around N-CS. Bandgap reduction in V2 O5 /N-CS nanocomposite (1.95 eV). 95% degradation of BPA under optimized condition. Discussed the degradation pathway of BPA with the support LC-MS results.